CONCEPTUAL ART AND HISTORY: Challenges of poetic construction in the 1970s (Palíndromo, 2017)
The Brazilian’s 70’s was a period fil-led with complexity: in one hand there was the dictatorship, with persecutions, torture and lack of freedom, and on the other hand, there was an increasing in the art movement. Unfortunately, most researches are focused in the discussions of music and theater fields and few stu-dies worked with visual arts. At the pre-sent work, artistic features developed in the 70’s will be analysed, taking into ac-count awards, critics and works of the Art Saloons promoted by the city council of Belo Horizonte (Salões de Arte da Prefei-tura de Belo Horizonte, in Portuguese) as a baseline. The art work of Miguel Gonti-jo will be contemplated.
Keywords: vanguard; conceptual art; contemporary art; museum